Point defects in ordered metallic compounds. I. Electronic-structure calculation by the linear-muffin-tin-orbital method - C. Koenig; N. Stefanou; J.M. Koch (Physical Review B, 1986)
The general formalism describing the electronic structure of dilute impurities in ordered compounds within the linear-muffin-tin-orbital approximation is presented. It is derived by considering the proper limit in the Green-function theory within the multiple-scattering formalism. The method thus obtained retains the advantages of the Green-function method for ab initio self-consistent calculations, but with reduced numerical efforts. We discuss in great detail several important aspects of its practical application towards point defects in cubic ordered metallic compounds; the part played by Friedel's screening rule, the calculation of the charge perturbations induced in the host, and the use of the complex-plane integration method are especially stressed.